NEW TRENDS IN CYBERCRIME IN THE MALDIVES - MOVING BEYOND LEGAL MEASURES IN THE NEW NORM - Fathimath Waheeda (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
INTRODUCTION The health emergency crisis due the COVID-19 pandemic has created challenges globally. The same applies to the Maldives, as lockdown and social distancing measures was enforced, the use of virtual communication by public authorities, businesses and individuals likewise increased. The new normal of working from home, video conferencing and meetings, online learning and shopping have created a large group of vulnerable users, providing more opportunities for cybercriminals to exploit. In a time where resources are diverted to fight against the COVID-19 pandemic, the law enforcement, investigative and judicial procedures may be delayed or disrupted due to compulsory prevention measures. The changing face of cybercrime needs to be addressed through non-legal measures to reduce the detrimental effect. OBJECTIVES New cybercrimes have emerged during the pandemic, which has affected the vulnerable users in a difficult and unprecedented time. The objective of the study is to identify the nature of cybercrime, including the emerging crimes and to examine how these issues could be addressed through legal and non-legal measures. METHODOLOGY The methodology adopted is through the study of secondary data collected through research of recent articles, legal statutes and newspaper articles from March 2020 until present. The data collected was applied through study, observation and analysis. SIGNIFICANCE This study will identify the emerging crimes during the pandemic, and bring together different approaches, including non-law measures to highlight the best method to address this issue. FINDINGS/RESULTS Forms of cybercrimes identified as prevalent in the country, namely (1) misinformation; (2) phishing and (3) privacy issues. Misinformation and disinformation regarding the virus, cures and conspiracies plays a key role in undermining the public trust and the effectiveness of the public safety measures. The ability to take action through legal measures were limited due inabilty to investigate, non-existence of applicable provisions, underreporting and late reporting amongst others. Non-legal measures such as awareness campaigns and cyber-education were utilised to empower vulnerable groups, especially children and seniors against emerging new forms of cybercrimes. CONCLUSIONS With the changing face of cybercrime and the prolonged uncertain future due to COVID-19, there should less reliance on the law and more proactive measures enacted at all levels to reduce the harmful effects.